Evaluation of pre-service teachers' classroom management skills during teaching practice in rural communities - Mkhasibe, R.G.; Mncube, D.W. (South African Journal of Higher Education, 2020)
This study investigated the classroom management skills which are implemented by B.Ed. pre-service teachers to create and maintain an appropriate environment that is favourable for teaching and learning. It used a qualitative methodology. One of the universities in KwaZulu-Natal was used as a case study. Sixteen third-year B.Ed. pre-service teachers who were placed in uMkhanyakude District schools were purposively selected and observed during their teaching practice, and five subject mentors were interviewed to find out how they view student teachers’ capabilities of classroom management. The findings revealed that the pre-service teachers were less confident about classroom management skills because they were struggling to manage their classrooms while the efforts by subject mentors had little impact on how classes are managed. For instance, they were not exposed to the established basic rules to reinforce the consequences of misbehaviour. This suggests that subject mentors have to step up the effort to close the gap as they are given the responsibility of mentoring pre-service teachers. They have to accompany pre-service teachers to classrooms and spend as much time as is necessary with them as part of confidence-building measures. Furthermore, the institutions in question have to upscale their classroom management programmes to ensure that pre-service teachers can cope with practical realities and dynamic conditions in the classroom to manage better during teaching practice.